Doses de potássio e umidades de solo para o crescimento de plantas de mogno-africano - Perez, Bruna Aparecida Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective this work was the evaluation of effects caused by potassium doses and soil moisture levels on growth of young african mahogany (Khaya senegalensis) plants growing in pots. Doses of 0, 50, 100, 150, and 200 mg dm-3 of K2O, combined with two soil moisture levels, i.e., 30 and 70% of the soil maximum water retention capacity, were the treatments applied to the plants. The treatments were replicated five times and distributed in the greenhouse according to a completely random design in the factorial scheme. When the plants growing in the 70% moisture soil were 180 days of age, they showed values of potassium efficiency use, stomata conductance, transpiration, photosynthesis, height, diameter, leaf area, root and stem and leaves dry matter content larger than those observed when soil moisture was of 30%. When soil moisture was of 30%, increasing doses of K determined increments in leaf area and leaves dry matter. Under conditions of moisture restriction, water use maximum efficiency was attained with a dose of 71 mg dm-3 of K2O. When soil moisture content was of 70%, increasing doses of K reduced the foliar concentration of N whereas P and K had their concentrations increased. Young african mahogany plants demand low amounts of K at their initial stage of growth provided that the other nutritional needs are met. In water restriction treatments, potassium increases the water use efficiency and leaves biomass

Objetivou-se avaliar os efeitos de doses de potássio no crescimento de plantas jovens de mogno-africano (Khaya senegalensis) submetidas a duas condições hídricas.Foram aplicados 0, 50, 100, 150 e 200 mg dm-3 de K2O combinados com duas condições hídricas: 30 e 70% da capacidade máxima de retenção de água do solo em vaso, no delineamento inteiramente casualizado e esquema fatorial 5 x 2, com cinco repetições. Aos 180 dias, as plantas apresentaram maior eficiência do uso do potássio, condutância estomática, transpiração, fotossíntese, altura, diâmetro, área foliar, matéria seca de raiz, caule e folhas, a 70% de umidade do que a 30%. A 30% de umidade, doses crescentes de K aumentaram a área foliar e matéria seca de folhas. Com restrição hídrica, a máxima eficiência de uso da água foi obtida com a dose 71 mg dm-3 de K2O. A 70% de umidade, doses crescentes de K diminuíram a concentração foliar de nitrogênio e aumentou as concentrações de fósforo e potássio. Plantas de mogno-africano são pouco exigentes em potássio na fase inicial de crescimento desde que as demais necessidades nutricionais sejam atendidas. Nos tratamentos de restrição hídrica, o potássio aumenta a eficiência do uso da água e a biomassa de folhas
Keywords: Mogno; Fotossintese; Potassio na agricultura; Crescimento (Plantas); Agua na agricultura; Photosynthesis